2010
DOI: 10.1111/j.1556-4029.2009.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Estimation Using Thoracic and First Two Lumbar Vertebral Ring Epiphyseal Union

Abstract: Union of the vertebral centra or "ring" epiphyses occurs during adolescence and early adulthood, providing valuable age at death information. We present a system for estimating age based on the timing and pattern of vertebral ring union. Data from 57 known individuals aged 14-27 years were used to establish age ranges for various patterns of union in females and males. Female age ranges were more well defined with less overlap in patterns of union than male age ranges. The age ranges are accompanied by descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
27
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 6 publications
(16 reference statements)
3
27
0
1
Order By: Relevance
“…Individuals were considered to be aged between 20 and 21 years when their third molars were completely developed, but overall epiphyseal and vertebral ring fusion and sternal rib end deterioration (Iscan et al, 1984(Iscan et al, , 1985Albert and Maples, 1995;Scheuer and Black, 2000;Albert and McCallister, 2004) suggested that an individual was 20 to 21 years. Age estimations for this group should be treated with some caution.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals were considered to be aged between 20 and 21 years when their third molars were completely developed, but overall epiphyseal and vertebral ring fusion and sternal rib end deterioration (Iscan et al, 1984(Iscan et al, , 1985Albert and Maples, 1995;Scheuer and Black, 2000;Albert and McCallister, 2004) suggested that an individual was 20 to 21 years. Age estimations for this group should be treated with some caution.…”
Section: Methodsmentioning
confidence: 99%
“…The age range over which these changes typically occur is extremely variable among modern adolescents (Marshall, ), and may have been more so in the past, given the greater disparity in environmental conditions and exposure to stress between different populations over time. Although we can assess the biological age of older children with relative accuracy (Albert and McAllister, ; Cardoso, ), we are so far unable to map puberty.…”
Section: Mineralization Of the Mandibular Canine Rootmentioning
confidence: 99%
“…Beyond the study of other age indicators from the presacral spine, such as the morphometrics of the fetal vertebra (Kósa and Castellana, 2005) or the size and shape of osteophytes in the mature and old adult spine (Stewart, 1958; Snodgrass, 2004; Watanabe and Terazawa, 2006), the literature has shown few studies dealing with the fusion of secondary ossification centers in the vertebral column. Apart from anatomical texts, which report a basic outline of the age ranges and broad patterns of development and fusion (e.g., Scheuer and Black, 2000), the only studies that provide fusion times are those carried out by McKern and Stewart (1957) for the thoracic vertebrae, Buikstra et al (1984) for the cervical vertebrae, Albert and Maples (1995), and Albert et al (2010) for thoracic and first two lumbar vertebrae. One other study (Veschi and Facchini, 2002) also provides fusion timing for vertebral epiphyses, but here no detailed data can be found for each individual vertebra and secondary center of ossification since they have all been pooled.…”
mentioning
confidence: 99%
“…McKern and Stewart (1957) document the timing of union in the annular rings of the vertebral bodies and the spinous process, while Buikstra et al (1984), Albert and Maples (1995), and Albert et al (2010) provide fusion times for the annular rings of the vertebral bodies. Due to limitations and specificities in their own samples, union data provided by McKern and Stewart (1957) and Buikstra et al (1984) are truncated inferiorly at the age of 17 years, and these studies included only males and females, respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation